2013
DOI: 10.5194/asr-10-33-2013
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of plume dispersion within various actual urban areas

Abstract: Abstract. Plume dispersion of hazardous materials within urban area resulting from accidental or intentional releases is of great concern to public health. Many researchers have developed local-scale atmospheric dispersion models using building-resolving computational fluid dynamics. However, an important issue is encountered when determining a reasonable domain size of the computational model in order to capture concentration distribution patterns influenced by urban surface geometries. In this study, we carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Many investigations have been devoted to better understanding of flow and pollutant dispersion in urban areas (e.g. Britter and Hanna, 2003;Rotach et al, 2004;Edussuriya et al, 2011;Nakayama et al, 2013;Panagiotou et al, 2013). One of the crucial factors that affect flow and pollutant dispersion in urban areas is buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have been devoted to better understanding of flow and pollutant dispersion in urban areas (e.g. Britter and Hanna, 2003;Rotach et al, 2004;Edussuriya et al, 2011;Nakayama et al, 2013;Panagiotou et al, 2013). One of the crucial factors that affect flow and pollutant dispersion in urban areas is buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The release location and measuring points are shown in Figure 3. In our previous study, it was shown that the spatial extent of concentration distribution patterns significantly influenced by urban surface geometries is a few hundred meters from a point source (Nakayama et al [27]). By comparing with the experimental data of the high-frequency concentration fluctuations measured in the very short range, we estimate prediction accuracy for the area where individual urban buildings largely influence the formation of plume concentration distributions.…”
Section: Dataset Of the Field Experiments For Estimating Prediction Amentioning
confidence: 99%
“…According to the building morphological analysis by Kanda et al [13], the horizontal average scale of urban buildings ranges from 14.5 to 19.5 m. In this case, the horizontal grid spacing less than about 1.0 m is required for accurate results. In addition, we have investigated a necessary computational domain size to capture the spatial extent of distribution patterns of plume concentrations influenced by urban surface geometries by LES comparative analysis [14]. It was shown that centerline mean concentration distributions for various urban areas are converging for downwind distances from the point source greater than 1.0 km and concluded that a necessary horizontal domain size of a computational model is at least 1.0 km.…”
Section: Computational Settingsmentioning
confidence: 99%